Ligamento periodontal em dentes extraídos amostra representativa do serviço público de Santa Maria -RS - Maier, Juliana (2014)
Periodontal diseases are highly prevalent and one of the most significant causes of tooth loss in the world, which is associated with functional, psychological, social and aesthetic impacts. The aim of this study was to evaluate the area of remaining periodontal ligament (ALPR) on extracted teeth collected in the public health care service to Santa Maria - RS. 725 teeth extracted teeth in five month period were collected, 414 were stained with hematoxylin 5% and analyzed with 7.5X increase in stereomicroscope to measure the ALPR. Chips containing reasons of extraction, age and gender of patients were record by dentists who performed the procedures. Descriptive analysis was calculated for demographic parameters, types of teeth extracted and reasons for extraction. Percentage of ALPR was determined for each tooth. Comparisons of ALPR area and total area between teeth extracted for periodontal reasons and other reasons were performed. Teeth extracted for periodontal reason were stratified cutoff points (25.40 and 50%) regarding the amount of remansecente periodontal ligament. ALPR extracted teeth by periodontal reason was extracted from 34.86% and 79.56% for other reasons (p = 0.00). Periodontal disease is the main reason reported for extraction (36.4%), followed by residual roots (21.4%). Upper molar (18.5%) and lower molar (44.5%) had the highest percentage of extraction for periodontal reasons and others, respectively. We conclude that, through an appropriate periodontal treatment and preventive periodic maintenance, a significant portion of the extracted teeth for periodontal reason could have been kept in comfort and function throughout life.